Keterbukaan Diri Tentang Gaya Hidup Hedonis Remaja SMA Negeri 1 Samarinda pada Media Sosial Instagram - Resa Septy Saputri; Endang Erawan; Kheyene Molekandella Boer (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
Instagram is a social media that is very popular with teenagers. Through its features, adolescents can show themselves (self-disclosure), including in presenting a hedonic lifestyle. The purpose of this study was to determine, describe and analyze self-‐‑disclosure about the hedonistic lifestyle of SMA Negeri 1 Samarinda adolescents on social media Instagram. This research use desciptive qualitative approach. The research focus refers to the dimension of self-disclosure based on aspects of the hedonic lifestyle. The results showed that the adolescents of SMA Negeri 1 Samarinda were active in self-disclosure about their activities spending time outside the home. This study also analyzes the negative impact of self-disclosure about a hedonic lifestyle, namely the existence of bad assessments of adolescents at SMA Negeri 1 Samarinda from other Instagram users. While the positive impact is the number of new friendships that have been established. There is no motivation and goals that underlie the teenagers of SMA Negeri 1 Samarinda to open themselves about the hedonistic lifestyle.